Time course of lymphocyte profile after femoral bone fracture - E. V. Davydova; M. V. Osikov; K. S. Abramov (Медицинская иммунология)
Isolated fractures of femur account for more than 10% of all road traffic injuries. Traumatic injury of femoral bone triggers a cascade of interrelated neuroendocrine reactions at systemic level, primarily at the hypothalamic-pituitary-adrenal axis, systemic response of immune system, initiated by release of tissue degradation products, cytokines and other mediators of damage into systemic blood circulation. Specific cellular reactions in response to traumatic injury to bone tissue include both innate and adaptive immune responses. In this regard, there is still scarce information on changes in blood lymphocyte subpopulations observed after closed isolated fracture of the femoral diaphysis at the middle third, before and after surgery. The aim of the present study was to evaluate the subpopulations of peripheral blood lymphocytes following closed isolated fracture of the femoral diaphysis with bone displacement in thecourse dynamics of surgical treatment, thus being required for studies in pathogenesis, development of diagnostic criteria and creating innovative treatment approaches. The study included 20 apparently healthy men and 36 men with closed isolated fracture of the femoral diaphysis of the middle third (32A and 32B, by AO/ASIF clinical classification, coded according to ICD-10 S72.3). The exclusion criteria were as follows: exacerbation of chronic comorbidities, diseases of lymphatic system and haematopoietic organs, oncological diseases, and evidence of osteoporosis. The spectrum of blood lymphocyte subsets was assessed on days 5, 7 (immediately after surgery) and on day 18 after closed isolated fracture of femoral diaphysis. We have found that, on the day 5 after IPBC along with leukocytosis in peripheral blood, the number of T-regulatory cells, cells with markers of early (CD25+) and late activation (HLA-DR+) proved to be increased, whereas representation of NK cells was decreased. On the day 7 after IPBC and immediately after surgery, leukocytosis persisted in blood, along with increased number of T-regulatory cells, CD3+ cells with early and late activation markers. On the day 18 after closed isolated fracture of the femoral diaphysis, the total numbers of leukocytes, T-lymphocytes, T-helpers, T-regulatory cells, T cells with an early activation marker are restored in peripheral blood, whereas the number of T-lymphocytes expressing HLA-DR+ molecules showed a significant increase.